Mathematics Learning during the Pandemic Era in Elementary School (Teacher's Perspective) - Dwi Kurniasih; Wahyudin (International Conference on Elementary Education, 2022)
This research aimed to analyze and describe mathematics learning during the pandemic at the Elementary School (SD) level from the teacher's point of view. The research approach used was quantitative through survey methods. Data were collected by a questionnaire and analyzed by descriptive statistics. The research subjects consisted of 60 respondents who worked as elementary school teachers. The results showed that teaching materials, methods, media, and evaluation tools in teaching mathematics during the pandemic were quite varied. The types of complicated mathematics learning to teach were principled learning and problem solving, with the kind of error students often make a technical error (calculation procedure). The obstacles experienced by teachers include students who do not understand the material, limited time, limited parental assistance, and limited facilities and infrastructure. Referring to these obstacles, the teacher believed that to make mathematics learning effective, they need to explore the selection of methods and media, approach with parents, complete facilities and infrastructure, master technology, and time management.